A Mesozoic Andean-Type Orogenic Cycle in Southeastern China as Recorded by Granitoid Evolution - Zhu, Kongyang; Li, Zheng-Xiang; Xu, X; Wilde, Simon (American Journal of Science, 2014)
Petrology, magnetic susceptibilities, zircon U-Pb ages, zircon Hf isotopes and whole-rock geochemical data are used to constrain the evolution of Mesozoic high-potassium granitic rocks that record an Andean-type orogenic cycle in the southeastern China segment of the Western Pacific. Decreasing melting pressures of the granitic magmas from the Late Triassic to the Early Cretaceous, as reflected by decreasing Sm/Yb ratios, point to a general trend of crustal attenuation with time in western Zhejiang Province. Five distinct stages of granitic magmatism are identified: (1) 230 to 215 Ma: high-temperature, high-pressure dehydration melting in a reduced and thickened crust caused by flat-slab subduction of the paleo-Pacific Plate; (2) 170 to 150 Ma: low-temperature, high-pressure water-fluxed melting in an oxidized and thickened crust caused by the foundering of the paleo-Pacific Plate; (3) 140 to 130 Ma: low-temperature, low-pressure dehydration melting of the continental crust caused by extension of the lithosphere; (4) 130 to 125 Ma: high-temperature, low-pressure dehydration melting of the refractory materials in the continental crust caused by further extension of the lithosphere and possibly basaltic underplating; and (5) 115 to 100 Ma: emplacement of fractionation products of hydrous basalts from the enriched continental lithospheric mantle.